Fluid catalytic co-processing of bio-oils with petroleum intermediates: Comparison of vapour phase low pressure hydrotreating and catalytic cracking as pretreatment. (15th October 2021) - Eschenbacher, Andreas; Myrstad, Trond; Bech, Niels; Thi, Hang Dao; Auersvald, Miloš; Van Geem, Kevin M.; Jensen, Anker D.
Highlights: Straw derived fast pyrolysis oils with ~7–8 wt% O were co-processed with FCC feed. 20/80 bio-oil/fossil feed blends showed ~2.5 percentage-points lower conversion. Increased yields of dry gas, CO, CO2, and coke at expense of naphtha. Observations attributed to high aromaticity and basic nitrogen content of bio-oils. Abstract: For co-processing of bio-oil and conventional fossil feed in existing refinery fluid catalytic cracking (FCC) units, little attention has been paid to the increased aromatics and basic nitrogen content in the feed associated with the introduction of bio-oil and how it affects FCC performance. In this contribution, the effect of blending two bio-oils obtained from different catalytic treatment of wheat-straw pyrolysis vapors with atmospheric residue was tested using a microactivity testing unit (MAT). The catalysts used for the pyrolysis vapor phase upgrading included i) a Na/γ-Al2 O3 deoxygenation catalyst, and ii) a Pt/TiO2 catalyst in combination with H2 atmosphere. The oxygen content of both bio-oils was similar at ~ 7–8 wt%, but the Na/γ-Al2 O3 bio-oil had a lower total acid number (TAN) of 5 mg KOH/g and a higher basic nitrogen (BN) content of 0.7 wt% compared to the Pt/TiO2 bio-oil (15 mg KOH/g, 0.4 wt% BN). The processing of the upgraded bio-oils in blends with atmospheric residue in MAT increased the yields of dry gas, CO, CO2, and coke at the expense of naphtha (decrease by 2.8 percentage points) and decreased the conversion by ~ 2.5 percentage points. This is attributed to the high aromaticity and basic nitrogen content of the two bio-oils. The lower basic nitrogen content and higher degree of saturation for the Pt/TiO2 bio-oil may explain its slightly higher conversion (by ≤ 1 percentage points) compared to the Na/γ-Al2 O3 bio-oil. This contribution provides important information for refinery operators interested in FCC co-processing of fossil oils and biomass-derived pyrolysis oils with elevated content of nitrogen and aromatics.